Catalyzing Henry reactions in chloroaluminate ionic liquids - Kumar, Anil; Pawar, Sanjay S. (Journal of Molecular Catalysis A - Chemical, 2005)
Henry reactions can be accelerated in chloroaluminate room temperature ionic liquids. The choloroaluminates with higher compositions of organic species of the chloroaluminates prove to be more efficient rate promoters than the ones with lower organic species in catalyzing Henry reactions. involving both aliphatic and aromatic carbonyl compounds. The ionic liquids can be recycled five times to offer good yields. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: chloroaluminates; Henry reactions; ionic liquids; Recycling